A Practical Guide to the Net-Map Approach: A Toolbox for Collaborative Research Design for Climate Action - Habermann, Birgit; Kibet, Walter; Getahun, Elizabeth; Kirwa, Annita (International Livestock Research Institute, 2025)
Net-mapping is a mapping tool based on group interviewing to visualize and discuss situations where many different actors can influence processes and outcomes. A net-map helps to understand which actors are involved in the network, the nature of their linkages, the extent of their influence (on what and whom), and what their goals are. The purpose of using net-mapping is to visualize and analyses how different stakeholders are connected and who plays key roles within a system. A network includes all relevant actors, such as individuals, organizations, companies, institutions, or groups, and the social or functional relationships or resource flows that link them. Net-mapping workshops are a space for group discussions and collaborative analysis to better understand how different actors impact outcomes within a given social-ecological system. Net-mapping generates lists of key actors and information on their relevance and influence, captured on flipcharts and later digitalised. Net-mapping supports stakeholder identification, assessment of influence, and reflective, participatory analysis.